2020
DOI: 10.1177/1369433220958765
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on stress-strain curves of seawater sea-sand concrete under uniaxial compression with different strain rates

Abstract: In order to investigate the mechanical properties of seawater sea-sand concrete (SSC) under uniaxial compression, the SSC prisms with different mix proportions are designed and prepared, and the compressive strength and stress-strain curves under uniaxial compression are tested, in which five loading strain rates 10−5/s, 10−4/s, 10−3/s, 10−2/s, and 10−1/s are selected. The failure patterns of the SSC specimens under different strain rates are discussed, and the peak stress, peak strain (strain at the peak stre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…This may be achieved due to fines in the manufacture of more paste volume. The compressive strength of mortar using M-Sand is consistently higher for all the mixes [23].…”
Section: Mechanical Properties Of Mortar 331 Compressive Strength For...mentioning
confidence: 84%
See 1 more Smart Citation
“…This may be achieved due to fines in the manufacture of more paste volume. The compressive strength of mortar using M-Sand is consistently higher for all the mixes [23].…”
Section: Mechanical Properties Of Mortar 331 Compressive Strength For...mentioning
confidence: 84%
“…From figure 10, it is clear that the peak stress rises as strain rate rises [23]. The behaviour of stress-strain for the various mixes begins with a straight line, indicating that stress-strain values are proportionate.…”
Section: Elastic Modulus or Modulus Of Elasticitymentioning
confidence: 92%
“…The test results of Group 7 further indicate that using seawater and sea-sand increased the concrete mixture’s early-age strength, but has less effect beyond 56 days. Zhang et al (2021) has previously concluded that this is mainly because chloride and sulfate ions catalyzes the hydration reflection, which can significantly improve the concrete’s early properties.…”
Section: Experiments Program and Test Resultsmentioning
confidence: 99%
“…In recent years, some achievements have been made in the study of seawater sea sand concrete. Xiao et al [3][4][5] reported many studies about mechanical behavior of seawater sea sand concrete. Huang et al [6] and Wu et al [7] studied the influence of mineral admixture on the performance of seawater sea sand concrete.…”
Section: Introductionmentioning
confidence: 99%